2021
DOI: 10.3389/fnhum.2021.760960
|View full text |Cite
|
Sign up to set email alerts
|

Postural Balance in Individuals With Knee Osteoarthritis During Stand-to-Sit Task

Abstract: Objective: Stand-to-sit task is an important daily function, but there is a lack of research evidence on whether knee osteoarthritis (knee OA) affects the postural balance during the task. This study aimed to compare individuals with knee OA and asymptomatic controls in postural balance and identify kinematic and lower extremity muscle activity characteristics in individuals with knee OA during the stand-to-sit task.Methods: In total, 30 individuals with knee OA and 30 age-matched asymptomatic controls perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
(65 reference statements)
3
24
0
1
Order By: Relevance
“…2 A]). High-certainty evidence with large effect from 4 studies (402 participants) [ 54 , 56 , 59 , 67 ] showed greater trunk flexion in individuals with knee OA compared to controls during sit-to-stand (SMD = 0.088, 95% CI = 0.58–1.18; Z = 5.80, P = 0.001 [Fig. 2 B]).…”
Section: Resultsmentioning
confidence: 99%
“…2 A]). High-certainty evidence with large effect from 4 studies (402 participants) [ 54 , 56 , 59 , 67 ] showed greater trunk flexion in individuals with knee OA compared to controls during sit-to-stand (SMD = 0.088, 95% CI = 0.58–1.18; Z = 5.80, P = 0.001 [Fig. 2 B]).…”
Section: Resultsmentioning
confidence: 99%
“…Knee Osteoarthritis (KOA) is a multifactorial condition characterized by pain, transient morning stiffness, crepitus on joint motion, that directly impact the quality of life of the individual (1) . KOA is furthermore associated with weakness of the quadricep and hamstring muscles due to atrophy caused by disuse and / or deficits in muscle activation, which promotes loss of balance and postural oscillation (2) .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of KOA pathological processes are complex and unclear. Studies have shown that it starts from the degenerative changes of knee articular cartilage, gradually affects the subchondral plate and joint capsule, and finally leads to the progressive destruction of articular cartilage and synovial inflammation [ 12 ]. Patients with KOA always have clinical symptoms such as joint pain, swelling, and mobility impairment [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%